2013
DOI: 10.7189/jogh.03.010405
|View full text |Cite
|
Sign up to set email alerts
|

Survey of caregivers in Kenya to assess perceptions of zinc as a treatment for diarrhea in young children and adherence to recommended treatment behaviors

Abstract: BackgroundIn 2004, the United Nations Children’s Fund (UNICEF) and the World Health Organization (WHO) revised their recommendations for management of acute diarrhea in children to include zinc treatment as well as oral rehydration solution (ORS). Little is known about how caregivers in low–resource settings perceive and use zinc treatment.MethodsUsing a semi–structured quantitative survey, we interviewed Kenyan caregivers who had used zinc to treat children aged 6–60 months with an episode of diarrhea during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
8
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 8 publications
3
8
0
1
Order By: Relevance
“…Although most Kenyan health care workers disagreed that antibiotics are the most effective treatment, approximately half of the antibiotics used by Kenyan caregivers at last episode were obtained from public facilities like those where most of the health care workers interviewed in Kenya were employed. The difficulties experienced by provider–training initiatives on treatment of pediatric diarrhea in developing countries [19] are consistent with our conclusions. Profitability also plays a role but to a lesser extent than is often imagined; for example, in Kenya the public sector provided about half of the antibiotics used to treat recent episodes of pediatric diarrhea.…”
Section: Discussionsupporting
confidence: 90%
“…Although most Kenyan health care workers disagreed that antibiotics are the most effective treatment, approximately half of the antibiotics used by Kenyan caregivers at last episode were obtained from public facilities like those where most of the health care workers interviewed in Kenya were employed. The difficulties experienced by provider–training initiatives on treatment of pediatric diarrhea in developing countries [19] are consistent with our conclusions. Profitability also plays a role but to a lesser extent than is often imagined; for example, in Kenya the public sector provided about half of the antibiotics used to treat recent episodes of pediatric diarrhea.…”
Section: Discussionsupporting
confidence: 90%
“…Its recommend that under-five years old children should receive 10–14 days of zinc treatment for diarrhea [ 11 ]. However, an increasing number of studies are showing that adherence to zinc is unsatisfactory [ 12 – 16 ]. A study in Kenya reported that among mothers who received diarrhea treatment for their children, 62 % reported giving zinc for fewer than the recommended 10 days [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In communities in Mali in which a zinc scale–up project was underway, adherence to 14 days of therapeutic zinc was 64% and though compliance with dosage instructions was generally good (94%), one infant received more than the age appropriate daily dose of zinc [ 14 ]. A cross–sectional study of caregivers of children under–five in Kenya reported low compliance with the guidelines on both zinc treatment duration (38%) and dosage (55%), with 32% of caregivers administering more than the age appropriate daily zinc dose [ 13 ].…”
mentioning
confidence: 99%